2022
DOI: 10.3390/cancers14153664
|View full text |Cite
|
Sign up to set email alerts
|

Li–Fraumeni Syndrome: Mutation of TP53 Is a Biomarker of Hereditary Predisposition to Tumor: New Insights and Advances in the Treatment

Abstract: Li–Fraumeni syndrome (LFS) is a rare familial tumor predisposition syndrome with autosomal dominant inheritance, involving germline mutations of the TP53 tumor suppressor gene. The most frequent tumors that arise in patients under the age of 45 are osteosarcomas, soft-tissue sarcomas, breast tumors in young women, leukemias/lymphomas, brain tumors, and tumors of the adrenal cortex. To date, no other gene mutations have been associated with LFS. The diagnosis is usually confirmed by genetic testing for the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 108 publications
0
12
0
Order By: Relevance
“…Inherited germline TP53 pathogenic and likely pathogenic mutations (TP53) cause autosomal dominant multicancer predisposition 33,34 . And one of the most iconic diseases is Li-Fraumeni syndrome (LFS) [35][36][37] . A study found that LFS men have a 25-fold increased risk of PCa compared with the general population 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Inherited germline TP53 pathogenic and likely pathogenic mutations (TP53) cause autosomal dominant multicancer predisposition 33,34 . And one of the most iconic diseases is Li-Fraumeni syndrome (LFS) [35][36][37] . A study found that LFS men have a 25-fold increased risk of PCa compared with the general population 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these clinical data suggested that tumors with PSMD14 overexpression in BC patients were significantly correlated with aggressive tumor characteristics. Multiple studies have confirmed that there are noticeable family genetic characteristics in the tumorigenesis of malignant tumors, such as ovarian cancers (BRCA1 and BRCA2 mutations) ( Heemskerk-Gerritsen et al, 2022 ), Li-Fraumeni syndrome (TP53 mutation) ( Rocca et al, 2022 ) and hereditary nonpolyposis colorectal cancer (DNA mismatch repair deficient) ( Liotta et al, 2021 ). Similarly, our study showed that patients with a family history of cancer were more likely to have high PSMD14 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Germline mutations in genes involved in DNA repair pathways are associated with genome instability and an increased risk of cancer development. For example, individuals with Li-Fraumeni syndrome are predisposed to various cancers, including leukemia, sarcomas, brain tumors, adrenocortical carcinoma, and other solid tumors, often manifesting at a young age ( 9 ). While TP53 germline mutations are frequently associated with Li-Fraumeni syndrome, some individuals with TP53-negative Li-Fraumeni syndrome harbor germline mutations in CHEK2 ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%